Bipolar Electrochemistry Regulation for Dynamic Meniscus Confined Electrodeposition of Copper Micro-Structures by a Double-Anode System. Issue 13 (1st January 2019) - Zhang, Xianyun; Zhang, Yifan; Li, Yanying; Lei, Yu; Li, Zhixiang; Sun, Aihua; Xu, Gaojie; Yu, Min-Feng; Guo, Jianjun
Abstract : Meniscus-confined electrodeposition (MCED) has emerged as a versatile additive micromanufacturing method for complex metal microstructures and flexible electrical interconnections. Up to now, common strategies for high-density and high-quality interconnections by MCED are focused on creating wire-based suspending 3D microstructures on conductive substrates, and neglect the fabrication process between various parts of the workpiece due to the ambiguous transition mechanism between different substrates. When spanning across an insulating substrate, the common two-electrode MCED process is not well suited for creating interconnections between polarized portions of adjacent parts due to the inevitable formation of bipolar electrodes (BPE), which induces the wire-bonding failure. Here, we describe an effective approach for manipulating the bipolar electrochemistry and suppressing the BPE-induced bonding failures in MCED, by using a double-anode system that facilitates the smooth electrochemical transition from insulating to conductive substrates. Based on this strategy, successful demonstrations of uniform interconnections with low electrical resistivity and high breakdown current density (∼6.56 × 10 10 A/m 2 ) are presented in the glass-gold transition area. This regulation strategy is potentially extendable to other electrochemical-processible materials for the next generation full 3D printed electronics and microdevices with the merits of enhanced integration density and low cost.